Arginase activity in alternatively activated macrophages protects PI3Kp110δ deficient mice from dextran sodium sulfate induced intestinal inflammation. Issue 11 (25th September 2014) - Weisser, Shelley B.; Kozicky, Lisa K.; Brugger, Hayley K.; Ngoh, Eyler N.; Cheung, Bonnie; Jen, Roger; Menzies, Susan C.; Samarakoon, Asanga; Murray, Peter J.; Lim, C. James; Johnson, Pauline; Boucher, Jean‐Luc; et al.
<x xml:space="preserve">Abstract</x> Alternatively activated or M2 macrophages have been reported to protect mice from intestinal inflammation, but the mechanism of protection has not been elucidated. In this study, we demonstrate that mice deficient in the p110δ catalytic subunit activity of class I phosphatidylinositol 3‐kinase (PI3Kp110δ) have increased clinical disease activity and histological damage during dextran sodium sulfate (DSS) induced colitis. Increased disease severity in PI3Kp110δ‐deficient mice is dependent on professional phagocytes and correlates with reduced numbers of arginase I+ M2 macrophages in the colon and increased production of inflammatory nitric oxide. We further demonstrate that PI3Kp110δ‐deficient macrophages are defective in their ability to induce arginase I when skewed to an M2 phenotype with IL‐4. Importantly, adoptive transfer of IL‐4‐treated macrophages derived from WT mice, but not those from PI3Kp110δ‐deficient mice, protects mice during DSS‐induced colitis. Moreover, M2 macrophages mediated protection is lost when mice are cotreated with inhibitors that block arginase activity or during adoptive transfer of arginase I deficient M2 macrophages. Taken together, our data demonstrate that arginase I activity is required for M2 macrophages mediated protection during DSS‐induced colitis in PI3Kp110δ‐deficient mice.